The Influence Of Using Google Earth Application-based learning Media In History Subject To Improve Learning Outcomes For Class C Students Of MAS Tahfidz Rokan Hulu: Pengaruh Penggunaan Media Pembelajaran Berbasis Aplikasi Google earth Dalam Matapelajaran Sejarah Untuk Meningkatkan Hasil Belajar Siswa Kelas X MAS Tahfidz Rokan Hulu - Arisma_05; Isjoni; Ananda Hasibuan, Rizki (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
In the current learning process, technology represents one of the systematic efforts in designing, implementing, and evaluating the entire learning process for a specific objective, combined with human resources to ensure that learning occurs effectively. Learning outcomes refer to the changes that occur in students after undergoing the learning process. History teachers at MAS Tahfidz Rokan Hulu have been effectively utilizing educational media derived from current technological developments during classroom instruction; however, the use of media remains lacking in variety. The objectives of this study are: (1) to examine the use of the Google Earth application in the history subject for Grade X at MAS Tahfidz Rokan Hulu, (2) to identify the effect of using the Google Earth application in history lessons on the learning outcomes of Grade X students at MAS Tahfidz Rokan Hulu, and (3) to understand the responses of Grade X students at MAS Tahfidz Rokan Hulu toward the use of the Google Earth application in history learning. This study uses a quantitative approach, with data collection techniques including observation, questionnaires, and documentation. The data analysis techniques employed are product-moment correlation and simple correlation analysis, using the variable of Google Earth application usage (X) and learning outcomes (Y). The statistical test results using SPSS for variable X (the influence of using Google Earth-based learning media) show a t-value = 5.887 > 2.002 = t-table, and sig = 0.000 < 5%. Therefore, H₀ is rejected. This means that the variable concerning the influence of using Google Earth-based learning media has a statistically significant effect on the dependent variable, which is students' history learning outcomes.